Endothelial RGS12 governs angiogenesis in inflammatory arthritis by controlling cilia formation and elongation via MYCBP2 signaling - Gongsheng Yuan; Shu-ting Yang; Shuying Yang (Cell Insight, 2022)
Angiogenesis is the formation of new capillaries that plays an essential role in the pathogenesis of inflammatory arthritis. However, the cellular and molecular mechanisms remain unclear. Here, we provide the first evidence that regulator of G-protein signaling 12 (RGS12) promotes angiogenesis in inflammatory arthritis through governing ciliogenesis and cilia elongation in endothelial cells. The knockout of RGS12 inhibits the development of inflammatory arthritis with the reduction in clinical score, paw swelling, and angiogenesis. Mechanistically, RGS12 overexpression (OE) in endothelial cells increases cilia number and length, and thereby promotes cell migration and tube-like structure formation. The knockout of cilia marker protein Intraflagellar transport (IFT) 80 blocked the increase in cilia number and length caused by RGS12 OE. Moreover, the results from LC/MS and IP analysis showed that RGS12 is associated with cilia-related protein MYC binding protein 2 (MYCBP2), which enhances the phosphorylation of MYCBP2 to promote ciliogenesis in endothelial cells. These findings demonstrate that upregulation of RGS12 by inflammation enhances angiogenesis by promoting cilia formation and elongation via activation of MYCBP2 signaling during inflammatory arthritis pathogenesis.